THE FUTURE OF EDUCATION WITH ENGLISH AND TECHNOLOGY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article discusses the future of education with the help of English language and modern technologies. Today, technology is changing the educational system around the world. English has become an international language of science, technology, and communication. The article explains how digital technologies and English language skills improve learning processes, communication, and professional development. It also analyzes the advantages of online education, artificial intelligence, and digital learning platforms in modern education.
Keywords: education, English language, technology, online learning, digital education, artificial intelligence, communication.